A comparative investigation of the technoeconomic feasibility and sustainability of mango waste biorefineries in South Africa: a process modeling approach - Manhongo, Tariro Tecla (Stellenbosch : Stellenbosch University, 2023)
Thesis (MEng)--Stellenbosch University, 2023.